Secondary battery and electronic device including the same

By setting two layers of graphite particles on the negative electrode of the secondary battery and adding specific additives to the electrolyte, the problem of uneven temperature and material during the high-rate charging and discharging of the secondary battery is solved, and the battery performance is improved and the life is extended.

CN119905586APending Publication Date: 2025-04-29NINGDE AMPEREX TECHNOLOGY LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510387215.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

During the high-rate charging and discharging process, existing secondary batteries face the problems of sharp increase in temperature and uneven reaction of electrode materials, resulting in a shortening of battery life and degradation of performance.

Method used

A secondary battery is designed, with the negative electrode including two layers of graphite particles, the porosity of the first layer is 0.1% to 3.5%, and the porosity of the second layer is 10% to 17%, and a specific additive is added to the electrolyte to suppress the side reaction between the anion and the electrolyte and reduce the impedance of the interface of the negative electrode.

Benefits of technology

Through this design, the charging and discharging performance of secondary batteries is significantly improved at high magnifications, and the battery has a high high-magnification charging and discharging capacity, which extends the battery's service life and reduces safety hazards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905586A_ABST
    Figure CN119905586A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery and an electronic device including the same. The secondary battery comprises a positive electrode, a negative electrode and an electrolyte, the negative electrode comprises a negative electrode current collector, a first negative electrode active material layer and a second negative electrode active material layer, the first negative electrode active material layer and the second negative electrode active material layer are arranged on the surface of the negative electrode current collector and are adjacent to each other, and the first negative electrode active material layer comprises first graphite particles; the porosity of the first graphite particles is 0.1%-3.5%; the second negative electrode active material layer comprises second graphite particles, and the porosity of the second graphite particles is 10%-17%; the ratio W1 / W2 of the width W1 of the first negative electrode active material layer to the width W2 of the second negative electrode active material layer is 0.17-3.00; the electrolyte contains an additive, and the additive comprises at least one of compounds shown in a formula 1-1 and a formula 1-2: # imgabs 0 # formula 1-1 and # imgabs 1 # formula 1-2. By adopting the design, the charge-discharge performance of the secondary battery under high rate can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a negative electrode for a secondary battery and an electrolyte for a secondary battery, and in particular to a secondary battery and an electronic device including the secondary battery. Background Art

[0002] With the rapid development of science and technology, various application fields have put forward higher and higher requirements on the performance of secondary batteries. Among them, the high-rate charge and discharge performance has become a key technical issue that needs to be improved. In many practical scenarios, such as the demand for fast charging of electric vehicles and some special electronic equipment applications with extremely high response speed requirements, the battery needs to complete a large amount of charge transfer in a short period of time, that is, to achieve high-rate charge and discharge.

[0003] However, existing secondary battery technology faces many challenges during high-rate charging and discharging. On the one hand, high-current charging and discharging will cause a sharp increase in heat generation inside the battery. Excessive temperature will not only accelerate the aging and decomposition of battery materials, shorten the battery's service life, but may also cause safety hazards; on the other hand, high-rate charging and discharging can easily cause uneven reactions on the surface of battery electrode materials, causing the battery's capacity to decay rapidly, seriously affecting the battery's overall performance and reliability. Therefore, how to effectively improve the charging and discharging performance of secondary batteries at high rates has become the focus and hot topic of current research in the field of secondary batteries. Summary of the invention

[0004] In view of this, the first aspect of the present application provides a secondary battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode current collector, a first negative electrode active material layer and a second negative electrode active material layer arranged on the surface of the negative electrode current collector, the first negative electrode active material layer and the second negative electrode active material layer are adjacent to each other, and there are a plurality of adjacently arranged first negative electrode active material layers and second negative electrode active material layers on the surface of the negative electrode current collector; the first negative electrode active material layer comprises first graphite particles, and the porosity of the first graphite particles is 0.1% to 3.5%; the second negative electrode active material layer comprises second graphite particles, and the porosity of the second graphite particles is 10% to 17%; the ratio W1 / W2 of the width W1 of the first negative electrode active material layer to the width W2 of the second negative electrode active material layer is 0.17 to 3.00; The electrolyte includes an additive, and the additive includes at least one of the compounds represented by Formula 1-1 and Formula 1-2: Formula 1-1, Formula 1-2.

[0005] In one embodiment, based on the mass of the electrolyte, the content of the additive is 0.2% to 2%.

[0006] In one embodiment, based on the mass of the electrolyte, the content of the additive is 0.5% to 1.3%.

[0007] In one embodiment, the width W1 of the first negative electrode active material layer is 0.5 mm to 2.4 mm; and / or the width W2 of the second negative electrode active material layer is 0.8 mm to 2.9 mm.

[0008] In one embodiment, W1 is from 0.8 mm to 2.1 mm; and / or, W2 is from 1.2 mm to 2.7 mm.

[0009] In one embodiment, based on the mass of the first negative electrode active material layer, the mass of the first graphite particles accounts for 90% to 98%.

[0010] In one embodiment, the first negative electrode active material layer further comprises second graphite particles; based on the mass of the first negative electrode active material layer, the mass proportion of the second graphite particles in the first negative electrode active material layer is 40% to 60%.

[0011] In one embodiment, a ratio W1 / W2 of a width W1 of the first negative electrode active material layer to a width W2 of the second negative electrode active material layer is 0.30 to 1.50.

[0012] In one embodiment, the additive is Formula 1-1.

[0013] A second aspect of the present application provides an electronic device, comprising the above-mentioned secondary battery.

[0014] Compared with the prior art, this application has the following beneficial effects: The present application arranges two negative electrode active material layers containing first graphite particles and second graphite particles respectively on the negative electrode current collector, controls the width ratio of the two different negative electrode active material layers, and adds specific additives to the electrolyte. By adopting the above-mentioned design of the negative electrode active material layer and the additive, the side reaction between the anions on the negative electrode surface and the electrolyte can be suppressed, the impedance of the negative electrode interface can be reduced, and the charge and discharge performance of the secondary battery at high rate can be improved, so that the secondary battery has a higher high-rate charge and discharge capacity. DETAILED DESCRIPTION

[0015] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0016] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the implementation or examples are included in at least one implementation or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same implementation or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more implementations or examples in a suitable manner.

[0017] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0018] According to the first aspect of the present application, the present application provides a secondary battery, which includes a negative electrode, a positive electrode, an electrolyte, and a separator disposed between the positive electrode and the negative electrode. The secondary battery can be a common battery in the art that can be used continuously by activating the active material by charging after the battery is discharged; in some embodiments, the secondary battery includes but is not limited to a lithium-ion battery.

[0019] In the present application, the electrolyte comprises a base solvent and an additive. The negative electrode comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The positive electrode comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector.

[0020] The present application mainly aims at improving and limiting the additives in the electrolyte and the composition of the negative electrode plate to obtain a secondary battery with improved high-rate charging performance.

[0021] Specifically, the negative electrode includes a negative electrode collector, a first negative electrode active material layer and a second negative electrode active material layer arranged on the surface of the negative electrode collector, the first negative electrode active material layer and the second negative electrode active material layer are adjacent, and there are multiple adjacently arranged first negative electrode active material layers and second negative electrode active material layers on the surface of the negative electrode collector; the first negative electrode active material layer includes first graphite particles, and the porosity of the first graphite particles is 0.1% to 3.5%; the second negative electrode active material layer includes second graphite particles, and the porosity of the second graphite particles is 10% to 17%; the ratio W1 / W2 of the width W1 of the first negative electrode active material layer to the width W2 of the second negative electrode active material layer is 0.17 to 3.00, and the electrolyte includes an additive, and the additive includes at least one of the compounds represented by Formula 1-1 and Formula 1-2: Formula 1-1, Formula 1-2; Preferably, the additive is Formula 1-1.

[0022] The inventors have found through research that in a secondary battery, when the electrolyte contains the additive and the negative electrode active material layer adopts the above design, the side reaction between the anions on the surface of the graphite negative electrode and the electrolyte can be suppressed, the interface impedance of the graphite negative electrode can be reduced, the charging performance of the secondary battery at a high rate can be improved, and the battery has a higher charge and discharge capacity.

[0023] In some embodiments, based on the mass of the electrolyte, the content of the additive accounts for 0.2% to 2%. As an example, the content of the additive may be 0.2%, 0.5%, 0.8%, 1.1%, 1.3%, 1.5%, 1.7%, 1.9%, 2%, etc. or a value within the range of any two of these values. When the content of the additive is within this range, the degree of side reactions can be further reduced, the ion transport on the surface of the graphite negative electrode can be improved, and the high-rate charge and discharge capacity of the secondary battery can be further improved. Preferably, the content of the additive accounts for 0.5% to 1.3%.

[0024] In some embodiments, the porosity of the first graphite particles is 0.1% to 3.5%. As an example, the porosity of the first graphite particles can be 0.1%, 0.4%, 0.6%, 0.9%, 1.2%, 1.5%, 1.8%, 2.1%, 2.4%, 2.8%, 3.2%, 3.5%, etc., or a value within a range composed of any two of these values. When the porosity of the first graphite particles meets the above range, the transmission distance of the active particles inside the graphite negative electrode can be shortened, reducing the occurrence of side reactions.

[0025] In some embodiments, the porosity of the second graphite particles is 10% to 17%. As an example, the porosity of the second graphite particles can be 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, etc. or a value within the range of any two of these values. When the porosity of the second graphite particles meets the above range, more active ions can be embedded under low impedance conditions, thereby improving the capacity preservation of the secondary battery.

[0026] In some embodiments, exemplarily, the ratio W1 / W2 of the width W1 of the first negative electrode active material layer to the width W2 of the second negative electrode active material layer can be 0.17, 0.19, 0.22, 0.25, 0.28, 0.32, 0.35, 0.38, 0.41, 0.45, 0.52, 0.55, 0.61, 0.65, 0.72, 0.75, 0.83, 0.88, 0.91, 1.2, 1.5, 2.2, 2.5, 3.2, etc. or a value within the range of any two of these values. In some preferred embodiments, the ratio W1 / W2 of the width W1 of the first negative electrode active material layer to the width W2 of the second negative electrode active material layer is 0.3 to 1.5; when W1 / W2 is within this range, the high rate charge and discharge performance of the secondary battery can be further improved.

[0027] In some embodiments, the width W1 of the first negative electrode active material layer is 0.5 mm to 2.4 mm. As an example, W1 can be 0.5 mm, 0.6 mm, 0.8 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm, 1.9 mm, 2.1 mm, 2.3 mm, 2.4 mm, etc., or a value within the range of any two of these values. When the width of the first negative electrode active material layer is within the above range, the lithium ion transport inside the graphite negative electrode can be further improved and the occurrence of side reactions can be reduced. Preferably, the width W1 of the first negative electrode active material layer is 0.8 mm to 2.1 mm.

[0028] In some embodiments, the width W2 of the second negative electrode active material layer is 0.8 mm to 2.9 mm. As an example, W2 can be 0.8 mm, 1.1 mm, 1.3 mm, 1.5 mm, 1.8 mm, 2.1 mm, 2.3 mm, 2.5 mm, 2.7 mm, 2.9 mm, etc. or a value within the range of any two of these values. When the width of the second negative electrode active material layer meets the above range, active ions such as lithium can be quickly embedded in the graphite negative electrode, greatly reducing the side reaction between the graphite negative electrode and the anions in the electrolyte. Preferably, the width W2 of the second negative electrode active material layer is 1.20 mm to 2.70 mm.

[0029] In some embodiments, based on the mass of the first negative electrode active material layer, the mass of the first graphite particles accounts for 90% to 98%.

[0030] In some embodiments, the first negative electrode active material layer further comprises second graphite particles; based on the mass of the first negative electrode active material layer, the mass proportion of the second graphite particles in the first negative electrode active material layer is 40-60%. In the present application, when the first negative electrode active material layer comprises both the first graphite particles and the second graphite particles, the adhesion between the negative electrode current collector and the graphite particles can be further ensured by the mutual cooperation of the two graphite particles, thereby ensuring that the battery has a higher charge and discharge capacity.

[0031] Furthermore, by controlling the mass ratio of the first graphite particles in the first negative electrode active material layer to the second graphite particles in the second negative electrode active material layer, the charge and discharge capacity of the secondary battery can be further improved. Preferably, the ratio of the content of the first graphite particles in the first negative electrode active material layer to the content of the second graphite particles in the second negative electrode active material layer is 6:4 to 3:7.

[0032] Electrolyte In addition to the above-mentioned additives, the electrolyte further includes an organic solvent, which may be, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate, propyl propionate, ethyl propionate, or methyl propionate. In some embodiments, other organic solvents include ether solvents, such as at least one of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME).

[0033] In the embodiment of the present application, the electrolyte includes a lithium salt as an electrolyte. The lithium salt in the electrolyte includes, but is not limited to: inorganic lithium salts, such as LiClO4, LiAsF6, LiPF6, LiBF4, LiSbF6, LiSO3F, LiN(FSO2)2; fluorine-containing organic lithium salts, such as LiCF3SO3, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,3-hexafluoropropane disulfonyl imide lithium, cyclic 1,2-tetrafluoroethane disulfonyl imide lithium, LiPF4(CF3)2, LiN(CF3SO2) (C4F9SO2), LiC(CF3SO2)3, LiPF4(CF3SO2)2, LiPF4(C2F5)2, LiPF4(C2F5SO2)2, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, LiBF2(C2F5SO2)2; lithium salts containing dicarboxylic acid complexes, such as lithium bis(oxalato)borate, lithium difluorooxalatoborate, lithium tris(oxalato)phosphate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate. In addition, the above-mentioned lithium salts can be used alone or in combination of two or more. For example, in some embodiments, the lithium salt comprises a combination of LiPF6 and LiBF4. In some embodiments, the lithium salt comprises LiPF6. In some embodiments, based on the mass of the electrolyte, the mass percentage of the lithium salt in the electrolyte is 10% to 20%.

[0034] The electrolyte also includes other additives. The additives that can be used in the electrolyte of the present application embodiment can be additives that are well known in the art and can be used to improve the electrochemical performance of the battery. In some embodiments, the additive includes but is not limited to at least one of polynitrile compounds, sulfur-containing additives, fluoroethylene carbonate (FEC), and 1,4-butane sultone.

[0035] The preparation method of the electrolyte in the embodiment of the present application is not limited and can be obtained according to the conventional preparation method of the electrolyte in the industry.

[0036] negative electrode In some embodiments, the first graphite particles and the second graphite particles include at least one of artificial graphite or natural graphite. Preferably, at least a portion of the surface of the first graphite particles is coated with amorphous carbon. Thus, the high rate charge and discharge capacity of the secondary battery is further improved.

[0037] The first graphite particles can be obtained by the following preparation method: crushing the coke raw material into a certain particle size, using a binder to condense to obtain a mixture, graphitizing the mixture at a temperature above 2600°C, and screening to obtain the first graphite particles. According to the particle size of the crushed raw material, the particle size of the mixture, etc., the porosity of the first graphite particles can be adjusted to 0.1% to 3.5%. For example, the particle size Dv50 of the crushed raw material is preferably 11μm~18μm. The porosity of the first graphite particles can be reduced by increasing the particle size of the crushed raw material.

[0038] The second graphite particles can be obtained by the following preparation method: crushing the coke raw material into a certain particle size, using a binder to condense to obtain a mixture, pressurizing the mixture into a block mixture, graphitizing the block mixture at a temperature above 2600°C, and crushing and screening the graphitized block mixture to obtain the second graphite particles. The porosity of the second graphite particles can be adjusted to 10% to 17% by adjusting the amount of volatiles in the mixture, such as a binder (such as asphalt) added to the coke raw material.

[0039] In some embodiments, the negative electrode active material may include a silicon-based material, such as a silicon-carbon material and / or a silicon-oxygen material, in addition to the first and second graphite particles used in the present application. In the negative electrode active material layer having the negative electrode active material including the first and second graphite particles, it is necessary to increase the contact point with the silicon-based material, thereby easily ensuring the contact point with the expansion and contraction of the Si-based material, ensuring the conductivity and the capacity of the secondary battery. Based on the mass of the negative electrode active material layer, the mass proportion of the silicon-based material is 1% to 10%, preferably 3% to 7%.

[0040] In some embodiments, the negative electrode active material layer further comprises a binder. The binder may include various binder polymers, such as polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc.

[0041] In some embodiments, the negative electrode active material layer further comprises a conductive agent to improve the electrode conductivity. Any conductive material can be used as the conductive material as long as it does not cause chemical changes. Examples of conductive agents include, but are not limited to: carbon-based materials, such as carbon black, acetylene black, Ketjen black, carbon fibers, etc.; metal-based materials, such as metal powders or metal fibers including copper, nickel, aluminum, silver, etc.; conductive polymers, such as polyphenylene derivatives, etc.; or mixtures thereof.

[0042] In some embodiments, the negative electrode current collector includes, but is not limited to: copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and any combination thereof. In some embodiments, the negative electrode current collector is copper foil.

[0043] In some embodiments, the preparation method of the negative electrode is a method for preparing a negative electrode that can be used for an electrochemical device that is well known in the art. Exemplarily, the negative electrode can be obtained by the following method: mixing the active material, the conductive agent, the binder and the above-mentioned negative electrode additive in a solvent, and heating the thickener as needed to prepare a negative electrode active material slurry, and coating the negative electrode active material slurry on the current collector, drying, and cold pressing to form a negative electrode active material layer. In some embodiments, the solvent may include, but is not limited to, water, N-methylpyrrolidone.

[0044] positive electrode The positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The specific types of the positive electrode active material are not subject to specific restrictions and can be selected according to needs.

[0045] In some embodiments, the positive electrode active material is a lithium transition metal oxide containing transition metal elements such as Co, Mn, and Ni. The lithium transition metal oxide can be, for example, Li x CoO2、Li x NiO2、Li x MnO2、Li x Co y Ni 1-y O2、Li x Co y M 1-y O z , Li x Ni 1-y M y O z , Li x Mn2O4、Li x Mn 2-y M y O4, LiMPO4, Li2MPO4F (M: at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3). They can be used alone or in combination. From the perspective of achieving a high capacity of a non-aqueous electrolyte secondary battery, the positive electrode active material preferably contains Li x NiO2、Li x Co y Ni 1-y O2、Li xNi 1-y M y O z Lithium nickel composite oxides such as (M: at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3).

[0046] In some embodiments, the positive electrode active material layer further includes a binder and optionally a conductive material. The binder can improve the bonding between the positive electrode active material particles and can improve the bonding between the positive electrode active material and the positive electrode current collector. In some embodiments, the binder includes, but is not limited to, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin and nylon, etc.

[0047] In some embodiments, the positive electrode active material layer also includes a conductive material to impart conductivity to the electrode. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., carbon black, acetylene black, ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.

[0048] In some embodiments, the positive electrode current collector is a metal, such as but not limited to aluminum foil.

[0049] In some embodiments, the preparation method of the positive electrode is a preparation method of the positive electrode that can be used for a secondary battery that is well known in the art. For example, the positive electrode can be obtained by the following method: mixing a positive electrode active material, a conductive material, and a binder in a solvent to prepare a positive electrode active material slurry, and coating the positive electrode active material slurry on a current collector, drying, and cold pressing to form a positive electrode active material layer. In some embodiments, the solvent may include water, N-methylpyrrolidone, etc., but is not limited thereto.

[0050] Isolation film In some embodiments, a separator is provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator are not particularly limited, and it can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.

[0051] For example, in some embodiments, the isolation film includes a substrate layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure. The material of the substrate layer can be selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, the material of the substrate layer can be selected from polypropylene porous film, polyethylene porous film, polypropylene non-woven fabric, polyethylene non-woven fabric or polypropylene-polyethylene-polypropylene porous composite film.

[0052] A surface treatment layer is provided on at least one surface of the substrate layer. The surface treatment layer can be a polymer layer, an inorganic layer or a layer formed by a mixed polymer and an inorganic substance. Specifically, the inorganic layer includes inorganic particles and a binder. The inorganic particles can be selected from one or more combinations of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The binder can be selected from one or more combinations of polyvinylidene fluoride, a polymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.

[0053] According to a second aspect of the present application, the present application provides an electronic device, which includes the above-mentioned secondary battery.

[0054] The use of the secondary battery of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. For example, the electronic device includes, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc. In addition, the secondary battery of the present application is applicable to energy storage power stations, sea transport vehicles, and air transport vehicles in addition to the electronic devices listed above. Air transport vehicles include air transport vehicles within the atmosphere and air transport vehicles outside the atmosphere.

[0055] The technical solutions of the embodiments of the present application are further described below through specific examples. Unless otherwise specified, the raw materials used in the following examples are all from common commercial products, and the devices or equipment used are all purchased from conventional market sales channels.

[0056] Example 1-1 1. Preparation of lithium-ion batteries: 1. Preparation of negative electrode Preparation of the first graphite particles: The particle size of coke is controlled to Dv50 of 9 μm, and a binder asphalt is added to the coke to obtain a mixture with a Dv50 of 12 μm. The mixture is high-temperature graphitized at a temperature of 2800°C, and then graded and sieved to obtain the first graphite particles with a Dv50 of 14 μm and a porosity of 0.9%.

[0057] Preparation of the second graphite particles: The particle size of the coke was controlled to be 12 μm at Dv50, and the binder asphalt was added to the coke to solidify it. A certain pressure was applied to obtain a density of 1.7 g / cm 3 The block mixture was graphitized at 2800°C. The graphitized block mixture was graded and sieved to obtain second graphite particles with a Dv50 of 14 μm and a porosity of 13%.

[0058] The first graphite particles, the second graphite particles, the conductive agent carbon black, the binder styrene butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC) prepared above are added to the solvent deionized water at a mass ratio of 48:48:1.5:1.5:1, and are fully stirred and mixed to form a uniform first negative electrode slurry. The second graphite particles, the conductive agent carbon black, the binder styrene butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC) prepared above are added to the solvent deionized water at a mass ratio of 96:1.5:1.5:1, and are fully stirred and mixed to form a uniform second negative electrode slurry.

[0059] Use a die coater to coat the first negative electrode slurry and the second negative electrode slurry on the two sides of the negative electrode collector copper foil in sequence, with coating widths of 0.5 mm (W1) and 2.9 mm (W2), respectively. Dry and cold press to form a negative electrode active material layer, and then cut and weld the pole ears to obtain a negative electrode with appropriate width.

[0060] 2. Preparation of positive electrode The positive electrode active material is lithium nickel cobalt oxide (LiNi 0.88 Co 0.09 Al 0.03 O2), conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are mixed in a solvent N-methylpyrrolidone (NMP) at a mass ratio of 96.3:2.2:1.5, and fully stirred in a vacuum mixer to obtain a positive electrode slurry. The positive electrode material is coated on both surfaces of the positive electrode current collector aluminum foil, dried, and cold pressed to form a positive electrode active material layer, and then cut into pieces and welded to the pole ears to obtain the positive electrode.

[0061] 3. Preparation of electrolyte In a dry argon atmosphere glove box, propyl propionate (PP), ethyl propionate (EP), ethylene carbonate (EC), propylene carbonate (PC), and the compound shown in Formula 1-1 are mixed evenly, dissolved and fully stirred, and then lithium salt LiPF6 is added and mixed evenly to obtain an electrolyte. Based on the mass of the electrolyte, the mass percentage of lithium salt LiPF6 is 12.5%, the mass percentage of EP is 8%, the mass percentage of PP is 62%, the mass percentage of the compound shown in Formula 1-1 is 0.8%, and the remainder is ethylene carbonate (EC) and propylene carbonate (PC), and the mass ratio of EC to PC is EC:PC=2:1.

[0062] 4. Preparation of Isolation Membrane Polyethylene (PE) porous polymer film is used as the isolation membrane.

[0063] 5. Preparation of Lithium-ion Batteries The obtained positive electrode, isolation film, and negative electrode are stacked in order, so that the isolation film is placed between the positive electrode and the negative electrode to play an isolating role, and then wound to obtain a bare cell; the bare cell is placed in an outer packaging foil aluminum-plastic film, and the electrolyte is injected. After vacuum packaging, standing, formation and other process flows, a lithium-ion battery is obtained.

[0064] The preparation processes of Examples 1-2 to 1-12, Examples 1-17 to 1-18 and Comparative Examples 1 to 3 are basically the same as those of Example 1-1, except that the additives and their contents, W1, W2, and the values ​​of W1 / W2 are adjusted according to Table 1. Please refer to Table 1 for specific differences.

[0065] In Example 1-13, compared with Example 1-1, in addition to the additives and contents, W1, W2, and W1 / W2 values ​​being adjusted according to Table 1, the preparation processes of the first negative electrode slurry and the second negative electrode slurry are also different, specifically: The proportions of the first negative electrode slurry are: first graphite particles, silicon-carbon material, conductive agent carbon black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) in a mass ratio of 92:4:1.5:1.5:1; the proportions of the second negative electrode slurry are: second graphite particles, silicon-carbon material, conductive agent carbon black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) in a mass ratio of 92:4:1.5:1.5:1.

[0066] In Examples 1-14 to 1-16, compared with Example 1-1, in addition to the additives and contents, W1, W2, and W1 / W2 values ​​being adjusted according to Table 1, the preparation processes of the first negative electrode slurry and the second negative electrode slurry are also different, specifically: The ratio of the first negative electrode slurry is: first graphite particles, conductive agent carbon black, binder styrene butadiene rubber (SBR), thickener sodium carboxymethyl cellulose (CMC) in a mass ratio of 96:1.5:1.5:1; the ratio of the second negative electrode slurry is: second graphite particles, conductive agent carbon black, binder styrene butadiene rubber (SBR), thickener sodium carboxymethyl cellulose (CMC) in a mass ratio of 96:1.5:1.5:1.

[0067] 2. Test Method 1. Porosity test: Use an ion milling device (e.g., Hitachi High-Tec, IM4000PLUS) to obtain a cross section of the negative electrode active material layer along the thickness direction. Use a scanning electron microscope to take a backscattered electron image of the above cross section, and the magnification when taking the backscattered electron image is 3,000 to 5,000 times; read the above image into a computer, use image analysis software (National Institute of Health, ImageJ) to perform binarization, convert the particle cross section in the image to black, and convert the pores in the particle cross section to a white binary processed image. Select the first and second graphite particles with a particle size of 5μm~20μm from the binary processed image, and calculate the area of ​​the cross section of the graphite particle and the area of ​​the pores in the cross section of the graphite particle. Here, the area of ​​the cross section of the graphite particle refers to the area of ​​the area surrounded by the periphery of the graphite particle, that is, the area of ​​all cross-sectional portions of the graphite particle. In addition, the pores with a width of less than 3μm in the pores existing in the cross section of the graphite particle are set as internal pores. Then, the porosity of the graphite particles is calculated from the calculated cross-sectional area of ​​the graphite particles and the area of ​​the internal pores in the cross-sectional area of ​​the graphite particles (area of ​​the internal pores in the cross-sectional area of ​​the graphite particles × 100 / area of ​​the cross-sectional area of ​​the graphite particles). The porosity of the first and second graphite particles is the average value of 10 particles each.

[0068] 2. Performance test of lithium-ion batteries 2.1 High rate discharge capacity Each secondary battery was discharged at a constant current of 0.1C until the battery voltage became 3.0V, and then continued to discharge at a constant voltage until the current value became 0.05C; after standing for 30 minutes, fast charging was performed at a constant current of 0.7C until the battery voltage became 4.2V; after standing for 30 minutes, constant current discharge was performed at 1.5C with 2.5V as the termination condition, and the discharge capacity obtained at this time was the high-rate discharge capacity. This application uses the high-rate discharge capacity to represent the charge and discharge performance of the secondary battery at a high rate. Among them: A: 80% to 85%; B: 75% to 80% C: Less than 70%.

[0069] Table 1

[0070] Compared with the comparative example, it can be seen that when the ratio W1 / W2 of the width W1 of the first negative electrode active material layer to the width W2 of the second negative electrode active material layer is 0.17 to 3.00, and the electrolyte contains at least one additive of the compounds represented by Formula 1-1 and Formula 1-2, the high voltage charge and discharge performance of the battery is significantly improved. When the first negative electrode active material layer contains both the first graphite particles and the second graphite particles, the adhesion between the negative electrode current collector and the graphite particles can be further ensured, ensuring that the battery has a higher charge and discharge capacity.

[0071] Furthermore, when the ratio W1 / W2 of the width W1 of the first negative electrode active material layer to the width W2 of the second negative electrode active material layer is 0.3 to 1.5, and the width W2 of the second negative electrode active material layer is 1.2 mm to 2.7 mm, the high-rate charge and discharge capacity of the secondary battery can be further improved.

[0072] Furthermore, based on the mass of the electrolyte, when the content of the additive accounts for 0.5% to 1.3%, the high-rate charge and discharge capacity of the secondary battery can be further improved.

[0073] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the principles of the present application should be included in the protection scope of the present application.

Claims

1. A secondary battery comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The negative electrode comprises a negative electrode current collector, a first negative electrode active material layer and a second negative electrode active material layer arranged on the surface of the negative electrode current collector, the first negative electrode active material layer and the second negative electrode active material layer are adjacent to each other, and there are a plurality of the first negative electrode active material layers and the second negative electrode active material layers arranged adjacent to each other on the surface of the negative electrode current collector; the first negative electrode active material layer comprises first graphite particles, and the porosity of the first graphite particles is 0.1% to 3.5%; the second negative electrode active material layer comprises second graphite particles, and the porosity of the second graphite particles is 10% to 17%; the ratio W1 / W2 of the width W1 of the first negative electrode active material layer to the width W2 of the second negative electrode active material layer is 0.17 to 3.00; The electrolyte includes an additive, and the additive includes at least one of the compounds represented by Formula 1-1 and Formula 1-2: Formula 1-1, Formula 1-2.

2. The secondary battery according to claim 1, characterized in that: Based on the mass of the electrolyte, the content of the additive accounts for 0.2% to 2%.

3. The secondary battery according to claim 1 or 2, characterized in that: Based on the mass of the electrolyte, the content of the additive accounts for 0.5% to 1.3%.

4. The secondary battery according to claim 1 or 2, characterized in that: The width W1 of the first negative electrode active material layer is 0.5 mm to 2.4 mm; and / or the width W2 of the second negative electrode active material layer is 0.8 mm to 2.9 mm.

5. The secondary battery according to claim 4, characterized in that: W1 is 0.8 mm to 2.1 mm; and / or, W2 is 1.2 mm to 2.7 mm.

6. The secondary battery according to claim 1 or 2, characterized in that: Based on the mass of the first negative electrode active material layer, the mass of the first graphite particles accounts for 90% to 98%.

7. The secondary battery according to claim 1 or 2, characterized in that: The first negative electrode active material layer further comprises second graphite particles; Based on the mass of the first negative electrode active material layer, the mass of the second graphite particles in the first negative electrode active material layer accounts for 40% to 60%.

8. The secondary battery according to claim 1 or 2, characterized in that: A ratio W1 / W2 of a width W1 of the first negative electrode active material layer to a width W2 of the second negative electrode active material layer is 0.30 to 1.

50.

9. The secondary battery according to claim 1 or 2, characterized in that: The additive is Formula 1-1.

10. An electronic device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A ternary material of a high-nickel system and a high-capacity battery

    CN109167051A

  • Nonaqueous electrolyte secondary battery

    CN114830391A

  • Negative plate of lithium ion battery

    CN116053412A

  • Negative electrode for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

    CN116964773A

  • Secondary battery and electronic device including the same

    CN118156620A